Determinants of Motor Vehicle Tax (PKB) Imposition in Central Java Province (2003-2022) - Kristian Abillio Pratama; Dea Mustika Kusuma Wardani (Universitas KH. Abdul Chalim Mojokerto, 2025)
Central Java Province has excellent potential to increase the realization of Motor Vehicle Tax (PKB) revenue, which positively impacts the increase in Regional Original Revenue (PAD). However, achieving PKB revenue realization in specific years is within the predetermined revenue realization target. Therefore, the Central Java Provincial Government must optimize PKB revenue. This study aims to determine the factors that affect the realization of PKB revenue, to determine the contribution of PKB revenue realization to the realization of local tax revenue, and to provide alternative policy recommendations to increase the realization of PKB revenue. This research method uses multiple linear regression analysis using time series data for 20 years, contribution analysis by calculating the proportion of realization of PKB revenue to the realization of local tax revenue, and qualitative descriptive method with a literature study. The results of this study show that population, Gross Regional Domestic Product (PDRB) in the transportation sector, and PDRB per capita have a positive and significant effect on PKB revenue. In contrast, the number of motor vehicles negatively and significantly affects PKB revenue. Then, the contribution analysis produces findings that the realization of PKB revenue in Central Java Province is still classified as quite adequate, and the realization of PKB revenue contributes moderately to the realization of local tax revenue.